Bilingualism as a strategy to delay the onset of Alzheimer's disease - Klimova, Blanka; Valis, Martin; Kuca, Kamil (Clinical interventions in aging, 2017)
The purpose of this study is to explore original studies which provide evidence about the effects of bilingualism on the delay of the onset of dementia, specifically Alzheimer's disease (AD). A literature review was conducted in the world's acknowledged databases: Web of Science, Scopus, and MEDLINE. Altogether, 14 original studies focusing on the research topic were detected. These included six prospective cohort studies and eight retrospective studies. Both types of studies suggest different conclusions. The findings from the prospective cohort studies state that there is no association between bilingualism and the delay of the onset of AD, while the retrospective studies claim the opposite. Despite the negative results of the prospective cohort studies, more research should be conducted on bilingualism and its impact on the delay of the onset of AD, since the brain studies have brought positive findings as far as the enhancement of cognitive reserve is concerned.
Keywords: evidence; older people; review; mnohojazyčnost; Alzheimerova nemoc; Alzheimer Disease; Retrospective Studies; retrospektivní studie; lidé; kognitivní rezerva; Prospective Studies; Multilingualism; Humans; effectiveness; cognition; Cognitive Reserve; prospektivní studie